2009
DOI: 10.1021/jp907296n
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Template-Free Fabrication of Hollow Magnetite Nanospheres and Their Application as Potential Drug Carriers

Abstract: Monodispersed Fe3O4 nanospheres with hollow interior structures exhibiting high saturation magnetization of 83.0 emu g−1 were fabricated by a facile one-pot route. The fabrication process is very simple with only FeCl3·6H2O and anhydrous NaAc as the reactants in an ethylene glycol solution with no templates or surfactants involved. Field-emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and a superconducting quantum interference device magnetometer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 40 publications
6
74
0
Order By: Relevance
“…Figure 2 C showed that the lattice fringes were 0.253 nm, in good agreement with the values for {311} planes of cubic magnetite phase; and the same crystal orientation of different magnetite crystallites was observed. [26] The selected-area electron diffraction (SAED) pattern recorded on a single Figure S1B in the Supporting Information). Therefore, it could be concluded that each octahedron was a single crystal enclosed by eight {111} planes.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 C showed that the lattice fringes were 0.253 nm, in good agreement with the values for {311} planes of cubic magnetite phase; and the same crystal orientation of different magnetite crystallites was observed. [26] The selected-area electron diffraction (SAED) pattern recorded on a single Figure S1B in the Supporting Information). Therefore, it could be concluded that each octahedron was a single crystal enclosed by eight {111} planes.…”
Section: Resultsmentioning
confidence: 99%
“…80,[92][93][94] Li et al synthesized an HMCNC-based Dox-loaded nanomedicine with porous shell and tunable hollow chamber by a one-pot solvothermal process. 81 This HMCNC carrier had a high surface area of 41.2 m 2 /g and pore volume of 0.36 cm 3 /g, which contributed to high drugloading capacity.…”
Section: Mesoporous Magnetic Colloidal Nanocrystal Clustersmentioning
confidence: 99%
“…The maximum loading capacity was calculated to be 8 μg of R6G on 140 μg of starch-GNS. Compared to other reported materials [23][24], this higher loading capacity was attributed to the large specific surface area of starch-GNS and the strong - conjugation as well as hydrogen bonding interaction between starch-GNS and R6G.…”
Section: Page 13 Of 30mentioning
confidence: 60%